Agroforestry in the Andean Araucanía: An Experience of Agroecological Transition with Women from Cherquén in Southern Chile - Peredo-Parada, S; Barrera-Salas, C (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Agroforestry is a practice used for the establishment of integrated production systems as an economic alternative. In Chile, the most significant experiences have been developed with rainfed farmers in the central zone, where the arboreal component is the predominant one. This study analyses the agroecological transition process of a group of women from the Andean foothills of southern Chile in the establishment of an agroforestry system based on rosehip. The field work was developed in 4 stages: (1) problem survey and definition of strategy; (2) identification of an alternative market; (3) perception of the data collection work and; (4) implementation of a demonstration unit; which included (a) workshops and meetings for discussion, reflection, and feedback on what had been done and to agree on the actions to be implemented; and (b) the development of different activities to implement the actions agreed in the workshops and meetings. The results of this research show that agroecological projects open doors to the participation, visibility, and valorization of women’s work while moving towards sustainable agroforestry systems integrated into the landscape. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.